2020
DOI: 10.3390/nu12010254
|View full text |Cite
|
Sign up to set email alerts
|

Essential Amino Acid Supplement Lowers Intrahepatic Lipid despite Excess Alcohol Consumption

Abstract: Excess alcohol consumption is a top risk factor for death and disability. Fatty liver will likely develop and the risk of liver disease increases. We have previously demonstrated that an essential amino acid supplement (EAAS) improved protein synthesis and reduced intrahepatic lipid in the elderly. The purpose of this exploratory pilot study was to initiate the evaluation of EAAS on intrahepatic lipid (IHL), body composition, and blood lipids in individuals with mild to moderate alcohol use disorder (AUD). Fol… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 53 publications
2
7
0
Order By: Relevance
“…Finally, there were a few changes observed in hepatic phosphorus metabolites that would indicate greater hepatic membrane turnover, yet the absence of consistent findings is likely due to the lack of severe disease in our population [53]. These data demonstrate that EAA supplementation may lower liver fat across groups of individuals with a wide range of physical characteristics and disease states [25,33,39].…”
Section: Specific Mixture Of Eaamentioning
confidence: 64%
“…Finally, there were a few changes observed in hepatic phosphorus metabolites that would indicate greater hepatic membrane turnover, yet the absence of consistent findings is likely due to the lack of severe disease in our population [53]. These data demonstrate that EAA supplementation may lower liver fat across groups of individuals with a wide range of physical characteristics and disease states [25,33,39].…”
Section: Specific Mixture Of Eaamentioning
confidence: 64%
“…Conditions largely associated with aging have been a frequent target of EAA therapy, including sarcopenia [ 62 , 85 ], long-term-care-acquired infections [ 86 ], low physical function [ 63 ], and heart failure [ 40 , 87 , 88 ]. Beneficial effects of EAAs have also been reported in the following conditions or situations: rehabilitation [ 89–92 ]; stroke [ 93 , 94 ]; bed rest/immobilization [ 8 , 65 , 95–97 ]; peripheral artery disease [ 98 ]; renal failure [ 99–103 ]; inflammation [ 104 , 105 ]; critical illness [ 106 ]; lung cancer [ 107 ]; cystic fibrosis [ 108 ]; chronic obstructive pulmonary disease [ 109–111 ]; wound healing [ 112 ]; brain injury [ 113 , 114 ]; metabolic syndrome and cardiovascular risk factors [ 115–117 ]; obesity [ 118 , 119 ]; liver fat [ 115 , 120–122 ]; and diabetes [ 123–127 ]. Importantly, in all of these studies beneficial effects were observed despite the absence of control of the consumption of EAAs contained in dietary protein, implying the importance of the rapid and complete absorption of free EAAs in clinical circumstances in which digestion may be impaired and anabolic resistance is prevalent.…”
Section: Eaas and Clinical Conditions And Outcomesmentioning
confidence: 99%
“…Seven slices of thigh muscle CSA were imaged, quantified, and averaged using Osirix (Geneva, Switzerland) [15]. Determination of intrahepatic lipid was performed in our laboratory as previously described [12].…”
Section: Magnetic Resonance Imaging/spectroscopymentioning
confidence: 99%
“…Sampling and analysis of all metabolic, lipid, and hepatic blood panels were performed by LabCorp (1626, 30th Avenue, Fairbanks, AK) as previously described [12].…”
Section: Blood Measurementsmentioning
confidence: 99%
See 1 more Smart Citation